2016
DOI: 10.5539/ijbm.v11n5p140
|View full text |Cite
|
Sign up to set email alerts
|

Technological, Organisational and Environmental Aspects of Audit Technology Acceptance

Abstract: The purpose of this paper is to use the Technology, Organisation and Environment (TOE) framework to understand the audit technology adoption in audit firms. Previous studies have only looked from the viewpoint of individual auditors and do not use a framework in which to understand the audit technology adoption. The audit technology differs from other information technology adoption because audit tools change the way in which auditors carry their tasks. One of the major contributions in this study is to use th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The magnitude of direct influence of the organization context on auditor adoption of technology is 0.156. Our outcome is in line predecessor research in(Handoko, 2020;Rosli et al, 2016) Hypothesis 3, Environment context has significant effect on auditor adoption of technology. According to Table6, referred from the significance result 0.000 absolutely under 0.05, the t arithmetic 4.792 also higher that on table which is 1.96.…”
supporting
confidence: 89%
“…The magnitude of direct influence of the organization context on auditor adoption of technology is 0.156. Our outcome is in line predecessor research in(Handoko, 2020;Rosli et al, 2016) Hypothesis 3, Environment context has significant effect on auditor adoption of technology. According to Table6, referred from the significance result 0.000 absolutely under 0.05, the t arithmetic 4.792 also higher that on table which is 1.96.…”
supporting
confidence: 89%
“…The utilization of CAATs by inward reviewers is not new; however it has developed after some time as the expansion of data innovation utilization has created in organizations. 22 The unavoidable idea of data innovation, the ideal monetary and functional adaptability of present-day figuring innovation, and the internationally open and cutthroat a publicise influences that drive the pace of innovative development are together making a period of significant change in the commercial center for review robotization. [23][24][25] While reviewers have been somewhat effective in utilizing existing advances to robotize components of their capacities, the organizations they work with are likewise going through critical change themselves.…”
Section: Introductionmentioning
confidence: 99%
“…26 Numerous associations have picked to use refined data advances for fostering their business cycle support, just as working on their data handling exercises. 22 This expands the requirement for CAATs in such organizations to permit examiners to keep on having the option to play out their audit and observing assignments successfully, just as to assume essential parts during the time spent developing in these organizations all the more by and large.…”
Section: Introductionmentioning
confidence: 99%
“…Barzekar and Karami (2014) also found that organisational factors have considerable impact on successful implementation of IT in teaching hospitals in Iran while Esen and Ozbag (2014) found that organisational readiness variables such as organisational resources, support, policy and innovativeness positively influence electronic human resource management (e-HRM) application in Turkey. Reporting on technology acceptance of audit firms in Malaysia, Rosli, Siew and Yeow (2016) revealed that management support for promoting audit technology such as provision of financial resources, training and IT facilities is an important factor in audit technology adoption and utilisation.…”
Section: Resultsmentioning
confidence: 99%